MAGGOT BSF CULTIVATION DEVELOPMENT STRATEGY AS ECONOMIC RESILIENCE DURING PANDEMIC - 1 (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2021)
This research is motivated by the large amount of waste that accumulates in many areas in Indonesia, especially household organic waste. The accumulated amount of waste is caused by the processing that is still not optimal to reduce the capacity of the amount of waste. Mr. Bilal's maggot cultivation business is a proven effective way to reduce the capacity of household organic waste in his village. The purpose of this study was to study the profile of maggot cultivation in Karang Pilang District, to analyze the prospects for the development of maggot cultivation during the covid pandemic, to determine a cultivation development strategy that is in accordance with the conditions and potential in the city of Surabaya. The population used in this study were all maggot cultivators in the city of Surabaya. The sample in this study was Maggot BSF cultivator Mr. Bilal in Kedurus village, Karang Pilang sub-district, Surabaya. The sampling method is the Accidental Sampling technique. The method used in this research is descriptive qualitative method. Data analysis using descriptive-qualitative analysis, without using quantitative techniques. The price of maggot is set according to the expenses that have been incurred during the production process and add a percentage to the profit to get a profit. Marketing strategy, introduce more to consumers in order to increase income or more profit, provide the best service, implement a selling system by upholding honesty when explaining maggot with honest conditions, with this attitude consumers will be happy and like this place of cultivation.